Ets, Ap-1 and GATA factor families regulate the utrophin B promoter: potential regulatory mechanisms for endothelial-specific expression. - Perkins, K; Davies, K (2003)
Duchenne muscular dystrophy is caused by dystrophin deficiency, which can be prevented in the mdx mouse model by over-expression of an autosomal homologue, utrophin. Utrophin has two characterised full-length promoters, A and B. No data are available on the transcriptional regulation of B utrophin, which has been recently localised to the endothelium. Similar to characterised endothelial promoters, Ets and Ap-1 individually trans-activate the human B core promoter. Synergistic activation by GATA-2 and c-jun to the order of 20-fold was observed.